Reflective Teaching as a Tool for Teacher Professional Development - Riyanti, Dwi (English Education:Journal of English Teaching and Research, 2021)
Reflection has long been known as an important component for teacher professional development, and it has been widely researched. However, little is known about how teachers reflect on their teaching. Aiming at finding out how in-service English as a foreign language (EFL) teachers reflect on their teaching activities and how their self-reflection impacts their professionalism, the current study employs a qualitative case study as its research design. It involved six in-service EFL teachers at various levels of education, such as kindergarten, elementary, junior, and senior high schools, who were taking the postgraduate program in English Education at FKIP Universitas Tanjungpura as the research participants. The data for this study were obtained through questionnaires and interviews, as well as the written analysis of participants' teaching videos. After being analyzed qualitatively, the findings of this study indicate that most respondents reflect on their teaching activities at a very basic level. In relation to the impact of their reflective teaching on their professionalism, however, overall, respondents thought that their reflection activities helped them know their weaknesses and strengths in teaching, which encouraged them to become better teachers.